P707 Increasing abundance of faecalibacterium prausnitzii is associated with decreased intestinal inflammation in Crohn's disease: A longitudinal study. (16th January 2018) - Björkqvist, O; Repsilber, D; Seifert, M; Engstrand, L; Rangel, I; Halfvarson, J
Abstract: Background: Decreased abundance of Faecalibacterium prausnitzii has been reported in Crohn's disease (CD). 1 F. prausnitzii is a major producer of butyrate, known to inhibit intestinal inflammation. However, it is largely unknown to which degree the abundance of F. prausnitzii correlates with the inflammatory activity, and few studies have addressed this from a longitudinal perspective. 2 Methods: Faecal samples ( n = 59) were collected subsequently every third month from CD patients ( n = 9). A qPCR assay was applied to quantify the relative abundance of F. prausnitzii in relation to the total amount of bacteria. To assess the total capacity of gut microbiota to produce butyrate, we measured the gene copy numbers of the Butyryl-CoA: acetate-CoA transferase gene using qPCR. The concentration of faecal calprotectin (ELISA EK-CAL, Bühlmann Laboratories) was used as a proxy of the inflammatory activity. Results: No significant correlations between F. prausnitzii or the Butyryl-CoA: acetate-CoA transferase gene and f-calprotectin were observed in the total sample set. By analysing alterations between consecutive samples, we observed a negative correlation between the abundance of F. prausnitzii and the concentration of f-calprotectin (Figure 1; R = 0.38; p = 0.01). The difference in abundance of F. prausnitzii between two subsequent samples accounted for 14% of f-calprotectin variation ( R 2 = 0.14). There was no significant association between the microbiota's total capacity to produce butyrate and f-calprotectin ( R = 0.12; p = 0.42) when alterations between consecutive samples were assessed. Conclusions: Temporal changes in the abundance of F. prausnitzii are inversely correlated to changes in f-calprotectin, indicating that F. prausnitzii may have an impact on the inflammatory activity in CD. Considering that the gene copy numbers of the Butyryl-CoA: acetate-CoA transferase gene did not correlate with inflammatory activity, we propose that F. prausnitzii may primarily inhibit inflammation by non-butyrate dependent mechanisms. References: 1. Wright EK, Kamm MA, Teo SM, et al. Recent advances in characterizing the gastrointestinamicrobiome in Crohn's disease: a systematic review. Inflamm Bowel Dis, 2015. 2. Segain JP, Raingeard de la Blétière D, Bourreille A, et al. Butyrate inhibits inflammatory responses through NFkappaB inhibition: implications for Crohn's disease. Gut, 2000.